The giant tadpoles of Megaelosia jordanensis (Heyer, 1983) - Nogueira-Costa, Paulo; Almeida-Santos, Patricia; Cruz, Carlos Alberto Gonçalvez; Caramaschi, Ulisses (Zootaxa, 2012)
The genus Megaelosia Miranda-Ribeiro currently comprises seven species associated with Atlantic Rain Forest of southeastern Brazil. This genus is composed of big-sized diurnal frogs that live associated to lotic streams in forests (Giaretta, et al. 1993). Five out of seven Megaelosia species have its larvae described: M. apuana Pombal, Prado & Canedo; M. boticariana Giaretta & Aguiar; M. goeldii Baumann; M. lutzae Izecksohn & Gouvêa; M. massarti De Witte (Pombal et al. 200; Giaretta & Aguiar, 1998; Lutz, 1930; Nuin, 2003; Giaretta et al, 1993).